Expression and prognostic value of ING3 in advanced laryngeal squamous cell carcinoma - Barlak, Neslişah; Kuşdemir, Gülnur; Gumus, Rasim; Şahin, Abdulkadir; Gündoğdu, Betül; Karatas, Ömer Faruk; Tatar, Arzu (The European Research Journal, 2023)
Objectives: Laryngeal squamous cell carcinomas (LSCC) is one of the most common aggressive neoplasms of the head and neck region. There is a significant need for identification of successful and accurate prognostic markers to better estimate the clinical outcomes for LSCC patients. In this study, we aimed at analyzing the differential expressions of inhibitor growth (ING) family members and to evaluate the prognostic values of deregulated ING genes in LSCC. Methods: We investigated the relative expressions of ING genes in laryngeal tumor-normal tissue pairs in the mRNA level using quantitative real-time polymerase chain reaction and relative expression of ING3 in the protein level using Western Blot analysis. Results: The rate of genetic alterations of ING3 was relatively higher in head and neck cancer including LSCC. ING3 expression was significantly upregulated in LSCC tissue samples in both mRNA and protein level. Higher expression of ING3 was also correlated with poor disease-free survival of patients with head and neck cancer. Conclusions: Our findings assigned an oncogenic feature for ING3 in laryngeal cancer with a significant upregulation detected in advanced cases and suggested a vital prognostic potential for ING3.